Conditional macroeconomic forecasts: Disagreement, revisions and forecast errors - Alexander Glas; Katja Heinisch (Halle Institute for Economic Research (IWH), 2021)
Using data from the European Central Bank's Survey of Professional Forecasters, we analyse the role of ex-ante conditioning variables for macroeconomic forecasts. In particular, we test to which extent the heterogeneity, updating and ex-post performance of predictions for inflation, real GDP growth and the unemployment rate are related to assumptions about future oil prices, exchange rates, interest rates and wage growth. Our findings indicate that inflation forecasts are closely associated with oil price expectations, whereas expected interest rates are used primarily to predict output growth and unemployment. Expectations about exchange rates and wage growth also matter for macroeconomic forecasts, albeit less so than oil prices and interest rates. We show that survey participants can considerably improve forecast accuracy for macroeconomic outcomes by reducing prediction errors for external conditions. Our results contribute to a better understanding of the expectation formation process of experts.
urn:nbn:de:gbv:3:2-137503
Keywords: C53; D84; E02; E32; 330; assumptions; disagreement; forecast accuracy; forecast revisions; survey forecasts